Classifying compounds as prebiotics - scientific perspectives and recommendations - Hutkins, Robert; Walter, Jens; Gibson, Glenn R; Bedu-Ferrari, Cassandre; Scott, Karen; Tancredi, Daniel J; Wijeyesekera, Anisha; Sanders, Mary Ellen (Nature reviews. Gastroenterology & hepatology, 2025)
Microbiomes provide key contributions to health and potentially important therapeutic targets. Conceived nearly 30 years ago, the prebiotic concept posits that targeted modulation of host microbial communities through the provision of selectively utilized growth substrates provides an effective approach to improving health. Although the basic tenets of this concept remain the same, it is timely to address certain challenges pertaining to prebiotics, including establishing that prebiotic-induced microbiota modulation causes the health outcome, determining which members within a complex microbial community directly utilize specific substrates in vivo and when those microbial effects sufficiently satisfy selectivity requirements, and clarification of the scientific principles on which the term 'prebiotic' is predicated to inspire proper use. In this Expert Recommendation, we provide a framework for the classification of compounds as prebiotics. We discuss ecological principles by which substrates modulate microbiomes and methodologies useful for characterizing such changes. We then propose statistical approaches that can be used to establish causal links between selective effects on the microbiome and health effects on the host, which can help address existing challenges. We use this information to provide the minimum criteria needed to classify compounds as prebiotics. Furthermore, communications to consumers and regulatory approaches to prebiotics worldwide are discussed.